Experimental study of the susceptibility of a European Aedes albopictus strain to dengue virus under a simulated Mediterranean temperature regime. Issue 4 (27th July 2018) - Brustolin, M.; Santamaria, C.; Napp, S.; Verdún, M.; Rivas, R.; Pujol, N.; Talavera, S.; Busquets, N.
Abstract: Dengue virus (DENV) has re‐emerged in Europe driven by the geographic expansion of the mosquito species Aedes albopictus and Aedes aegypti (Diptera: Culicidae) and the introduction of the virus by viraemic travellers. In the present study, the vector competence (VC) of Ae. albopictus collected in Catalonia (northeast Spain) was evaluated for two different DENV strains, DENV‐1 and DENV‐2, the serotypes responsible for all outbreaks of dengue that have occurred in Europe. Mosquitoes were reared under environmental conditions mimicking the mean temperature and humidity recorded in July on the Mediterranean coast of Catalonia. Mosquitoes were fed on an artificial infectious bloodmeal and, at 14 days post‐exposure, infection, disseminated infection and transmission rates (IR, DIR, TR) and transmission efficiency (TE) were determined by testing the virus in the body, legs and saliva. The tested Ae. albopictus strain was found to be susceptible to both DENV‐1 and DENV‐2 and to be able to transmit DENV‐1. This is the first time that the VC of Ae. albopictus for DENV has been tested in Europe in this specific context (i.e. mimicking the Mediterranean temperature and humidity recorded in Catalonia in July). This study confirms the potential of Ae. albopictus to start autochthonous DENV transmission cycles in the Mediterranean basin. Abstract : The vector competence of Aedes albopictus (Diptera: Culicidae) for dengue virus (DENV) was carried out in conditions mimicking the Mediterranean temperature and humidity recorded in Catalonia (northeast Spain) in July. Aedes albopictus was susceptible to DENV serotypes 1 and 2 and was able to transmit DENV‐1, showing that vector susceptibility is dependent on the serotype of DENV. Viral RNA can be detected in the saliva of infected mosquitoes using FTA™ cards without the need to sacrifice the mosquitoes.